Human Papillomavirus Vaccine: A New Opportunity for The Treatment of Human Papillomavirus Infections - Ambwani, Sneha; Prakash, Prabhu; Surana, Seema; Bhansali, Suman (National Journal of Community Medicine, 2014)
NA